Differential thrombotic prolapse burden in either bioresorbable vascular scaffolds or metallic stents implanted during acute myocardial infarction: The snowshoe effect: Insights from the maximal footprint analysis. (1st October 2016) - Diletti, Roberto; van der Sijde, Jors; Karanasos, Antonios; Fam, Jiang Ming; Felix, Cordula; van Mieghem, Nicolas M.; Regar, Evelyn; Rapoza, Richard; Zijlstra, Felix; van Geuns, Robert Jan
Abstract: Background: The hypothesized increased thrombus entrapment during bioresorbable vascular scaffold implantation in acute myocardial infarction, the so-called "snowshoe effect" has never been demonstrated. Methods: Patients enrolled in the BVS STEMI FIRST study matched with STEMI patients implanted with everolimus-eluting metal stents (EES) and undergoing optical coherence tomography (OCT) at the index procedure were compared. Quantitative coronary angiography analysis and optical coherence tomography data for evaluation of thrombotic prolapse were reported. Percentage maximal footprint (%MFP) analysis as an indicator of the snowshoe effect was performed. Results: A total of 302 patients were analyzed (151 with BVS and 151 with EES). Of those patients 30 implanted with BVS and 17 implanted with EES were imaged at the index procedure with OCT. Baseline clinical characteristics, TIMI-flow and thrombus burden were similar between groups. Aspiration thrombectomy was similarly performed in the two groups (BVS 83.3% vs 94.1% EES, p = 0.405). At the end of the procedure, final TIMI 3 flow was achieved in 93.3% and 82.4% of BVS and EES patients respectively (p = 0.296). The %MFP was significantly higher in the BVS treated patients (36.59 ± 5.65% vs 17.61 ± 4.30, p < 0.001). The results of the OCT analysis showed a mean prolapse area (0.61 ± 0.26 mm 2 vs 0.90 ± 0.31 mm 2, p = 0.001) and a percentage prolapse area (7.11 ± 2.98 mm 2 vs 9.98 ± 2.90 mm 2, p = 0.002) significantly higher in the EES group. Conclusions: Scaffold structural characteristics such as strut width may play a role in terms of thrombus dislodgment patterns and acute prolapsing material.